Assessing fatty acid oxidation flux in rodent cardiomyocyte models - M. Rech (Nature Portfolio, 2018)
Abstract The healthy adult heart primarily relies on fatty acid oxidation (FAO) for energy production but instantaneously adapts its substrate preference in response to physiological or pathological challenges. Accurate FAO measurements are crucial to investigate early metabolic (mal)adaptations. While measurements in intact cardiomyocytes offer greater physiological relevance, current FAO protocols mainly employ cell-free systems and/or require expensive equipment. Here, we present an easy-to-use, inexpensive, and sensitive method to measure, compare and modulate FAO in various cardiomyocyte models. Basal FAO was 2-fold higher in fresh versus cultured adult rat cardiomyocytes (aRCM), while OXPHOS protein levels were maintained. Basal FAO was higher in cultured (3-fold) and fresh (8-fold) aRCM, versus widely used neonatal rat cardiomyocytes (nRCM) and mouse HL1 cardiomyocytes. Moreover, we utilized chemical and pharmacological treatments in order to modulate the FAO flux at different cellular signalling levels. Our data indicate that caution should be taken when studying metabolism in nRCM and HL1 cell models, as these display significantly lower FAO than aRCM. Accurate FAO measurement in cultured aRCM opens new avenues for studying the complex cardiomyocyte metabolic responses to mechanical, nutritional, pharmacological, and genetic manipulations.